(3eLehY Gdabgs - (3RjO Hf Ydj Hf GdMSjf Hf Ydj Hf CHj WGdH , CHh GdMSjf GdYdhqj GdgGTej GdbQTj , hjbGd dg (B((3RjO GdTgjO(B)(3,J (B122 (3g` s
(3ChdgG (B:s
(3CNHQfG GdTjN CMeO Hf GdMSjf MOKfi CHh NGdO YeQh Hf NGdO GdhGSWi , bGd (B: (3MOKfi RjO Hf Ydi Yf CHjg Ydi Hf CHj WGdH Ydjge GdSdGe , bGd QCjJ QShd Gddg Udi Gddg Ydjg hSde hBdg JhVC aZSd hLgg hPQGYjg KdGKkG s
(3BNQgG (B:s
(3BNQg ef hUa QShd Gddg Udi Gddg Ydjg hSde (B: (3QjM YQbI CWjH ef QjM GdeSc , de CQ bHdg hdG HYOg eKdg Udi Gddg Ydjg hYdi Bdg hSde s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B8s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B59 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B190s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI LGeY GdQhVI HVhGMi UfYGA s
Keywords: (3Gdabg GdESdGejs